(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2020)
Cork Fish (Channa striata) and Baung Fish (Mystus)is a fish that has a high nutritional value and many produced from the Musi City Palembang River. Activities in the region can produce waste that can harm water environment such as industrial waste and domestic household waste. This research aims to determine the level of heavy metals lead (Pb) in Cork fish (Channa striata) and Baung Fish (Mystus) originating from the Musi city of the river Palembang. Random sampling method on fish suppliers in the traditional market of Palembang by using the method of atomic absorption spetrophotometry. Based on the results of measurements made, heavy metal content of Pb Cork fish meat average of 0.1036 mg/kg and on average Baung fish meat 0.1425.As for the gills of the cork, the rate of Thymbalnya ranges between 0,0911-0,0953 mg/kg and in the gills of the fish range between 0,1117-0,1843 mg/kg. There are heavy metal contaminants in the meat as well as the fish Cork (Channa striata) and Ikan Baung (Mystus) derived from the waters of the Musi River that is the city of Palembang where the heavy metal levels lead to the fish is higher compared with fish meat.